ANALISIS MANAJEMEN RISIKO PADA SISTEM INFORMASI AKADEMIK MENGGUNAKAN FRAMEWORK OCTAVE ALLEGRO - Nadiya, Khoirun; Nila Choirun Nisa; Salsabila Annafi'u Nur Aini; Adinda Ummay Putri Sutan Jandi (Journal of Research and Publication Innovation, 2024)
Academic Information Systems can help universities in academic management. The Academic Information System is managed by the data center and information technology in which there are IT stakeholders. If universities cannot identify the source of threats, then the implementation of academic information systems can pose a risk. Therefore, risk management is needed to detect risk threats as early as possible so that risk prevention or mitigation can be carried out. Risk management is a structured action used for risk identification, assessment, and prevention. This research uses Octave Allegro which has 8 steps, including setting risk measurement criteria, profiling information assets, identifying information asset containers, identifying problem areas, identifying threat scenarios, identifying risks, analyzing risks, and selecting mitigation approaches. The Octave Allegro method is used to determine data security threats. The purpose of this research is to conduct a risk analysis of academic information systems which results in a risk assessment and recommendations related to things that need to be prevented or mitigated. The risk assessment is focused on predetermined areas of concern.